An analysis on skype a voip application / Nik Mohd Nazim Nik Zahari - Nik Zahari, Nik Mohd Nazim (2005)
Skype is a peer-to-peer VoIP client developed by KaZaa in 2003. Skype claims that it can work almost seamlessly across NATs and firewalls and has better voice quality than the MSN and Yahoo IM applications. It encrypts calls end-to-end, and stores user information in a decentralized fashion. Skype also supports instant messaging and conferencing. These researches analyze the voice packet in Local Area Network and also analyzing the security method of Skype application between users across the internet while using instant messaging services. This research is using Sniffer Pro to analyze the voice packet and Ettercap to sniff the Skype application while the user is using instant messaging services. After the analyzing has been done the result is that Skype application has a good quality voice and the delay is normal. Compare to other instant messaging services, Skype uses encryption method to encrypt the text to send to other user across the internet.